Refractive error and visual status of children with disability / Wan Norafikah Wan Abdullah - Wan Abdullah, Wan Norafikah (2016)
Purpose: The objective of this study was to determine the visual acuity and refractive error status among children with disability. Methods: The eye examination data were reviewed from Low Vision and Rehabilitation Clinic. Data of children with disability age from birth to 18 years old were selected. The age, gender, types of disability and eye examination which includes visual acuity, colour vision test, cover test, refraction, anterior segment and posterior segment were extracted and analyzed. Results: A total of 27 data of children with disability were reviewed. Among them, 55.5% had VA 6/18 or better, whereas 26% had VA 6/24 or worse. The percentage of children with disability having refractive error was 85.19%. Hyperopia was the common refractive error occurred among children with disability. Approximately 41.6% of children with disability had strabismus in which most of them had esotropia (25.9%). Majority of the children with disability that had strabismus were among Down syndrome children. Conclusion: Children with disability are prone to have vision disorder. Early eye examination and visual abnormality detection are needed among those children for better intervention prognosis.